Group size effects in cooperatively breeding African wild dogs - Gusset, M; Macdonald, D (Elsevier, 2010)
In groups of cooperative breeders, individual fitness can increase as a direct consequence of group size, whereby the extent of these benefits is likely to depend, to a degree that is largely unknown, on the prevailing ecological conditions. We examined the effect of group size on pup production and survival across age classes in cooperatively breeding African wild dogs, Lycaon pictus, across 12 quasiexperimental sites in South Africa varying in ecological conditions. In this sample spanning over 43 pack-years, group size had a significantly positive effect on litter size after emergence from the den, but not on number of pups surviving to 1 year of age or survival rates for pups, yearlings and adults. Stronger relationships between these variables have been reported in other samples, so these results might be explained by low competitor density and high prey availability in our study areas. This explanation is supported by the finding that neither of these variables had any significant effect on pup production and survival across age classes in the present study. The results of our quasiexperimental study suggest that varying ecological conditions represent an important source of intraspecific variation in the impact of helpers in cooperative breeders.